On Oral History in Translation and Interpreting Studies - Carsten Sinner (Chronotopos, 2020)
This contribution gives an overview of history and oral history, in particular with regard to the designation, delimitation, and definition of oral history; to methodological and general aspects and the problems associated with oral history; as well as to the issue of oral history and interdisciplinarity. After describing the relationship between history, Translation and Interpreting Studies, and oral history, it discusses the recourse of Translation and Interpreting research to oral history. This is followed by the presentation of the IALT Oral History of Translation and Interpreting project, where the project history, its objectives, and the project outline are addressed. Some initial insights and results will be produced with the aid of some examples from the ongoing research, concentrating on their relation to written sources—and to statistical data in the archives in particular—, and on how the oral history project interviews and the archive material can be mutually beneficial.